MEDITERRANEAN AFTER US PRESIDENTIAL ELECTIONS IN 2024: SCENARIO FOR THE NEAR FUTURE - Jankovic, Slobodan; Budimir, Željko (Serbian political thought, 2025)
American presidential elections in 2024 among other things are marked by Donald Trump’s announcement regarding changes in foreign affairs. In this moment of history, which was characterized by changing world order, the Mediterranean Sea, in particular Eastern and Southern parts, and the Balkans are areas in proximity or directly affected by conflicts. The paper starts with the assumption that change in the White House would imply a certain discontinuity in their foreign policy. By implementing the Italian neoclassical geopolitical framework, the authors question the hypothesis. In line with that approach, opposition between NATO and Russia is considered as among the elites marked by diverging cultural traits and histories. The paper is divided into four parts. In order to arrive at the outcomes of the Trump scenario (new presidential mandate of Donald Trump), importance of the South and East Mediterranean and the Balkans is analyzed from the geopolitical perspective and in the view of current global reordering. Finally authors conclude that change could occur vis-à-vis Ukraine, while US politics in the Middle East would follow the current stance.